What Has Changed in Patients Aged 65 and over Diagnosed with Breast Cancer during the COVID-19 Pandemic: A Single-Center Experience - Soyder, Aykut; Guldogan, Nilgun; Isiklar, Aysun; Aribal, Erkin; Basaran, Gul (KARGER, 2022)
Introduction: The COVID-19 pandemic has a worldwide negative impact on healthcare systems. This study aims to determine how the diagnosis, clinicopathological features, and treatment approaches of patients with breast cancer (BC) diagnosed at >= 65 years old were affected during the pandemic. This survey has shown that patients, especially the elderly, had to postpone their BC health problems or delay their routine controls due to the risk of COVID-19 transmission, high mortality rates due to comorbidity, and restrictions. Materials and Methods: The medical records of 153 patients with BC diagnosed at >= 65 years old before (January-December 2019

group A, n = 61) and during (March 2020-May 2021

group B, n = 92) the COVID-19 pandemic were retrospectively analyzed. In addition, clinicopathological features of patients, including age, admission form, clinical stage, tumor (T) size-grade-histology-subtype, lymph node involvement, surgery type, and treatment protocols, were evaluated. Results: Patients mostly applied for screening purposes were included in group A and patients who frequently applied for diagnostic purposes due to their existing BC or other complaints were included in group B (p = 0.009). Group B patients had a higher clinical stage (p = 0.026) and had commonly larger (p = 0.020) and high-grade (p = 0.001) Ts. Thus, mastectomy and neoadjuvant systemic therapy were more commonly performed in group B (p = 0.041 and p = 0.005). Conclusion: The survey showed significant changes in BC diagnosis and treatment protocols for patients diagnosed at >= 65 years old during the COVID-19 pandemic. Postponing screening and delaying treatment leads to more advanced BC stages in elderly patients. (C) 2022 S. Karger AG, Basel
Keywords: Elderly; Breast cancer; Corona virus disease 19; Pandemic; Treatment